Percepções e práticas dos atores em comunidades virtuais - Josué Laguardia; Ângela Oliveira Casanova; Rejane Ramos Machado (Universidade Estadual de Campinas, 2012)
The objective of this paper is to report the main features of a tool to manage virtual communities in the interaction processes, the conditions that favored or limited the construction of knowledge and how this practice occurred in virtual communities on a public federal level institution. The data were collected through semi-structured interviews with mediators and users of these environments. In the virtual communities studied, it was found that the initial proposal of creating a space for discussion and interaction was replaced by activities of information repository and administrative support. The use and purpose of this application was affected by both technical aspects and by the actions of its users. The mediation was absent from the learning spaces and the interaction was tied to the perception of usefulness of the tool. The challenge posed to the virtual communities coordinators is the conversion of these environments in collaborative workspaces.